St. Louis Paper - Geosynclines and Petroliferous Deposits (with Discussion) - Marcel R. Daly (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
In a preceding paper1 the writer has pointed out some apparent relationship between the distribution, on the surface of the globe,, of the known hydrocarbon deposits and the disposition of the principal zones of deformation of the earth's body (geosynclines). He wishes to present some further remarks on this subject. Petroleum deposits, or their derivatives or descendants, are found through the whole range of sedimentary strata, from the pre-Cambrian to the Quaternary. For instance, the prc-Beltian (Shuswap) series of the Canadian Cordillera are interbedded with limestones which are sometimes rich in carbonaceous matter (Sicamous limcstone); and the Beltian system of the same region contains layers of argillitcs and dolomitic limestones which are equally high in carbon content.2 This carbon may be interpreted as the last remnant of hydrocarbons previously contained in the rocks. On the other hand, the actual formation of hydrocarbons under conditions that would eventually permit their deposition in modern sediments is conceded by some geologists.3 Between these two extreme limits, bitumens are found indifferently in all sedimentaries. Thcy constitute a continuous series, some kind of a large family, whose individual members may be entitled to a community of origin and probably represent the different stages of evolution of the primitive, parent matter. The kinship between petroleum and such substances as asphalt, ozocerite, manjak, grahamite, albertite, etc., is well known; and E. H. Cunning-gam-Craig has recently shown how intimately shale fields and oil fields are connectcd.4 For this reason, no distinction is made in the present